2020
DOI: 10.3892/mmr.2020.10932
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a high‑fat diet on intestinal stem cells and epithelial barrier function in middle‑aged female mice

Abstract: a high-fat diet (HFd) or obesity-promoting diet is closely associated with metabolic diseases and intestinal tumors, particularly in middle-aged individuals (typically 45-64 years old). The intestinal epithelium constitutes a barrier that separates the host from the food and microbiota in the gut, and thus, a dysfunctional epithelium is associated with a number of diseases. However, the changes caused to the function of intestinal epithelium in response to an HFd have not been well-studied to date. in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 44 publications
6
44
1
Order By: Relevance
“…In our study, HFD reduced the size and weight of the gastrointestinal organs in accordance with previous studies performed in mice [39,40]. This reduction in the size of the organs could be due to the low-grade chronic inflammation associated with obesity, in which pro-inflammatory cytokines, such as tumor necrosis factor alpha (TNF-α) or interleukin-6 (IL-6), are increased [41].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, HFD reduced the size and weight of the gastrointestinal organs in accordance with previous studies performed in mice [39,40]. This reduction in the size of the organs could be due to the low-grade chronic inflammation associated with obesity, in which pro-inflammatory cytokines, such as tumor necrosis factor alpha (TNF-α) or interleukin-6 (IL-6), are increased [41].…”
Section: Discussionsupporting
confidence: 91%
“…Colon morphology can be altered by growth, digestion and absorption, immune regulation, and intestinal injury repair [46][47][48][49][50]. e V/C ratio can comprehensively reflect the digestive status of the intestinal tract and is directly proportional to the digestive and absorption capacity of the gut tract [51,52]. In the present study, the villi and recessus biopsy and statistical data showed that the high-dose aqueous extract could partly improve the defective morphology inside the colon.…”
Section: Discussionsupporting
confidence: 47%
“…And crypts were further likely to form mini‑intestine organoids in a 3D culture Barrier function of the small intestine is not altered by HFD. The proportion and count of Paneth cells was not altered in the small intestinal crypt derived from organoids Possibly the inflammatory factors and monocyte chemoattractant protein‑1 (MCP‑1) [ 79 ] 9 HFD in Drosophila Induced a transient activation of intestinal stem cells by microbiota Induces JNK signaling in enterocytes, which triggers production of the cytokine upd3, thereby activates STAT signaling in intestinal stem cells [ 78 ] 10 Hyperphagia db/db obese mouse model and a HFD-induced obesity mouse model fed with HFD (60% fat) for 8 weeks vs a standard chow diet ISCs division, villi length, and nutrient absorption increased in both models Upregulation of b-catenin protein along with inactivation of glycogen synthase kinase (GSK)-3b and Cyclin-D1, independent of leptin signaling [ 75 ] HFD (23% fat) vs 5% fat in control feed in a pig model Expanded colon stem cell zone and proliferative zone earlier onset of obesity and insulin resistance. induce inflammation in Proliferative zone, but not the stem cell zone the increase in inflammation mediators (TLR-4, NF-kB, LCN-2 and IL6) induced with intestinal bacterial flora dysbiosis [ 125 ] 11 Lgr5-EGFP-iresCreERT2 male and female mice.…”
Section: Intestinal Stem Cellsmentioning
confidence: 99%
“…For example, the type of diet and obese genetic model used in studies are not consistent. Comparing the type of high-fat diet (HFD), the difference in the amount of fat in the diet or the time and duration of treatment differs; [60% HFD ([ 77 ], 80 , 79 , 135 , 75 ) or 45% HFD; [ 22 ], 91 ], [low-fat ([ 80 ], 135 , 22 ) or chow ([ 77 ], 79 , 75 ], as well as [2–4 months; [ 80 ], 79 ; 135 , 75 ), 5–6 months [ 22 ] or 7–14 month [ 77 ]]. Nutrient components of feed also may vary in different studies.…”
Section: Complexities and Limitationsmentioning
confidence: 99%